The INNpinJeR: a new wall-free reactor for studying gas-phase reactions. Issue 1 (7th January 2022) - Scholz, Wiebke; Mentler, Bernhard; Fischer, Lukas; Berndt, Torsten; Hansel, Armin
Abstract : The Innsbruck wall free impinging jets reactor (INNpinJeR) is characterized by quantifying oxidation products of the well-understood ozonolysis reactions of tetramethyl ethylene and cyclohexene with an ammonium chemical ionization mass spectrometer. Abstract : Here we characterize the new Innsbruck wall free impinging jets reactor (INNpinJeR) and compare its performance with the TROPOS free jet flow system by quantifying oxidation products of the well-understood ozonolysis reactions of tetramethyl ethylene (TME) and cyclohexene with an ammonium chemical ionization mass spectrometer. We support the results with flow and chemical simulations on the k-ε RANS steady-state flow field. Flow simulations show a mixing region in the center of the reactor that does not disturb the surrounding laminar main flow. Quantitative detection of several peroxy radicals strongly suggests negligible wall contacts. Direct comparison with the TROPOS flow system using cyclohexene ozonolysis with the same analytical technique shows very good reproducibility. The total effective reaction time amounts to 9.0–9.3 seconds found from the flow and chemistry simulations and 9.4 ± 1.1 seconds according to the analysis of TME ozonolysis products. These features allow for characterizing the sensitivity of analytical instruments towards different oxidation products, including RO2 radicals, but most importantly we can conclude, that the Innsbruck wall-free INNpinJeR can be used to study gas-phase chemistry under atmospherically relevant conditions without significant influence of interface chemistry.